2017
DOI: 10.1158/1055-9965.epi-16-0106
|View full text |Cite
|
Sign up to set email alerts
|

The OncoArray Consortium: A Network for Understanding the Genetic Architecture of Common Cancers

Abstract: Background Common cancers develop through a multistep process often including inherited susceptibility. Collaboration among multiple institutions, and funding from multiple sources, has allowed the development of an inexpensive genotyping microarray, the OncoArray. The array includes a genome-wide backbone, comprising 230,000 SNPs tagging most common genetic variants, together with dense mapping of known susceptibility regions, rare variants from sequencing experiments, pharmacogenetic markers and cancer relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
385
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 312 publications
(390 citation statements)
references
References 81 publications
3
385
0
2
Order By: Relevance
“…Quality control steps follow the approach described previously for the OncoArray 5 (Supplementary Note). …”
Section: Methodsmentioning
confidence: 99%
“…Quality control steps follow the approach described previously for the OncoArray 5 (Supplementary Note). …”
Section: Methodsmentioning
confidence: 99%
“…This featured a meta-analysis of six existing GWAS and two new GWAS making use of the Illumina OncoArray (35), in total comprising 12,496 cases and 18,190 controls. The study identified 13 new glioma risk loci, five for GBM at 1p31.3 ( JAK1 ), 11q14.1, 16p13.3 (near MPG ), 16q12.1 ( HEATR3 ) and 22q13.1 ( SLC16A8 ), and 8 for non-GBM glioma at 1q32.1 ( MDM4 ), 1q44 ( AKT3 ), 2q33.3 (near IDH1 ), 3p14.1 ( LRIG1 ), 10q24.33 ( OBFC1 ), 11q21 ( MAML2 ), 14q12 ( AKAP6 ), and 16p13.3 ( LMF1 ).…”
Section: Chronological History Of Glioma Risk Loci Discoverymentioning
confidence: 99%
“…Genotyping of a subset of Sister Study participants was conducted using Illumina’s Infinium OncoArray-500K beadchip platform via participation in the GAME-ON consortium (49). The OncoArray panel includes a genome-wide backbone of 230,000 tag SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…Data cleaning and quality control filtering were conducted by the GAME-ON consortium, with further details described elsewhere (49). After these exclusions, 3,363 Sister Study participants (1829 in sub-cohort [including 67 cases] and 1534 additional cases) provided both genotype and 25(OH)D data.…”
Section: Methodsmentioning
confidence: 99%